Dynamic changes of mononuclear phagocytes in circulating, pulmonary alveolar and interstitial compartments in a mouse model of experimental silicosis. (28th July 2016) - Xiang, Guo-An; Zhang, Yi-Dan; Su, Cheng-Cheng; Ma, Yong-Qiang; Li, Yu-Ming; Zhou, Xin; Wei, Lu-Qing; Ji, Wen-Jie
Abstract: Context : Silicosis is a devastating, irreversible lung fibrosis condition exposed to crystalline silica. The mononuclear phagocyte system plays an important role in the pathogenesis of silicosis. Objective : The present study was aimed to explore the dynamic changes of mononuclear phagocytes in circulating, pulmonary alveolar and interstitial compartments in experimental silicosis model. Materials and methods : A mouse model of lung fibrosis was developed with crystalline silica particles (2 mg/40 μL via oropharyngeal instillation) using male C57BL/6 mice, and were killed on days 1, 3, 7, 14, and 28. The lung inflammation and fibrosis was investigated using hematoxylin–eosin staining and bronchoalveolar lavage fluid (BALF) analysis, Masson's trichrome staining, and immunofluorescence. Circulating monocyte subsets (Ly6C hi and Ly6C lo ), polarization state of BALF-derived alveolar macrophages (AMϕ) and lung interstitial macrophages (IMϕ, derived from enzymatically digested lung tissue) were analyzed by flow cytometry. Results : The percentage of Ly6C hi monocytes significantly increased on day 1 after silica exposure, which reached the peak level from day 7 till day 28. Moreover, M2 (alternative activation) AMϕ (PI − CD64 + CD206+) was dramatically and progressively increased from day 1 to day 28. A parallel increase in IMϕ with M2 polarization (PI-CD64 + CD11b + CD206+) was also observed from day 1 to day 28. Conclusion : Our data demonstrate a dynamic view of mononuclear phagocyte change in three compartments after silica challenge, which highlights the remodeling of mononuclear phagocyte system as a potential therapeutic target for silicosis.